Polarised neutron diffraction measurements of PrBa2Cu3O6+x and the Bayesian statistical analysis of such data - Markvardsen, AJ (2000)
The physics of the series PryY1-yBa2Cu3O6+x, and ability of Pr to suppress superconductivity, has been a subject of frequent discussions in the literature for more than a decade. This thesis describes a polarised neutron diffraction (PND) experiment performed on PrBa2Cu3O6.24 designed to find out something about the electron structure. This experiment pushed the limits of what can be done using the PND technique. The problem is one of a limited number of measured Fourier components that need to be inverted to form a real space image. To accomplish this inversion the maximum entropy technique has been employed. In some cases, the maximum entropy technique has the ability to increase the resolution of ‘inverted’ data immensely, but this ability is found to depend critically on the choice of constants used in the method. To investigate this a Bayesian robustness analysis of the maximum entropy method is carried out, resulting in an improvement of the maximum entropy technique for analysing PND data. Some results for nickel in the literature have been re-analysed and a comparison is made with different maximum entropy algorithms. Equipped with an improved data analysis technique and carefully measured PND data for PrBa2Cu3O6.24 a number of new interesting features are observed, putting constraints on existing theoretical models of PryY1-yBa2Cu3O6+x and leaving room for more questions to be answered.